Consultative workshop on the role of climate info data and services in Uzbekistan report - Anarbekov, Oyture (2023)
This workshop is based on CGIAR Regional Integrated Initiative F2R-CWANA WP5. The workshop sets itself the task of answering this question: “What kind of Climate Information Data and Services do participants need to manage climate risks in the CWANA region, in particular in Uzbekistan?” The consultative seminar within the framework of WP5 coincides with World Soil Day and World Mountain Day, which is celebrated jointly with the Committee of the Senate of the Parliament of the Republic of Uzbekistan on the development of the Aral Sea region.